Mole Cricket IPM Guide for Florida - C. R. Kerr; N. C. Leppla; E. A. Buss; J. H. Frank (EDIS)
Mole crickets can become serious pests of turfgrasses, pastures, and vegetable seedlings. The first step in determining if you have a mole cricket problem at a site is to compare the existing damage to pictures of known mole cricket damage. If the damage is likely caused by mole crickets, specimens should be obtained and the pest identified. You then should determine if the number of mole crickets is great enough to cause an unacceptable level of damage and decide what control measures should be used. Eventually, a long-term, sustainable integrated pest management (IPM) program should be established. This guide will help you identify mole cricket infestations and manage them effectively and economically while minimizing environmental impacts.